Researching the probation service response to mental health need - Sirdifield, Coral (Probation, mental health and criminal justice, 2023)
Approximately 39% of people on probation have a current mental illness. The Probation Service is a unique organisation within the Criminal Justice System. It represents a caring face of state correctional activities, and also has more punitive controlling duties which can fundamentally impinge on the lives and liberty of those supervised in the community. This combination of care and control in the Probation Officer role is well documented, presenting practising probation staff with complex professional challenges. Individuals researching mental health need in the probation population face a complex set of problems which this chapter explores. Access to data can be blocked at a very early stage of the research. The sensitive nature of stigmatisation associated with mental health conditions, lack of time and organisational apathy can provide barriers to research. The chapter explores some of the myriad of methodological challenges needing consideration when designing research in probation settings. This will include discussion around the use of in-depth interviewing, focus groups, telephone interviewing and survey methods. The chapter will end by asking who is intended to benefit from research in this area. Data can be used to effect policy change or ineffectively used to bolster professional careers.